2017
DOI: 10.3758/s13423-017-1306-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smiling on perceived age defy belief

Abstract: It is a common belief that smiling makes people appear younger. Empirical findings, however, suggest that smiling faces are actually perceived as older than neutral faces. Here we show that these two apparently contradictory phenomena can co-exist in the same person. In the first experiment, participants were first asked to estimate the ages of a series of smiling or neutral faces. After that, they were asked to estimate the average age of the set of neutral and smiling faces they had just evaluated. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 11 publications
(18 reference statements)
4
35
0
Order By: Relevance
“…From these results, Ganel and Goodale claimed that the belief that smiling makes one appear younger is a misconception rooted in popular media, given that smiling faces are not perceived as younger than faces with other expressions in direct evaluation. Ganel and Goodale's (2018) study provided evidence that age estimation differs between direct and retrospective evaluations; however, it has not yet been verified whether the belief that smiling makes one appear younger can be generalized across cultures. Ganel and Goodale's (2018) study had two limitations.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…From these results, Ganel and Goodale claimed that the belief that smiling makes one appear younger is a misconception rooted in popular media, given that smiling faces are not perceived as younger than faces with other expressions in direct evaluation. Ganel and Goodale's (2018) study provided evidence that age estimation differs between direct and retrospective evaluations; however, it has not yet been verified whether the belief that smiling makes one appear younger can be generalized across cultures. Ganel and Goodale's (2018) study had two limitations.…”
Section: Introductionmentioning
confidence: 82%
“…Ganel and Goodale's (2018) study provided evidence that age estimation differs between direct and retrospective evaluations; however, it has not yet been verified whether the belief that smiling makes one appear younger can be generalized across cultures. Ganel and Goodale's (2018) study had two limitations. First, Ganel and Goodale's results may have been affected by their use of faces selected only from the Karolinska Directed Emotional Faces (KDEF) database (Lundqvist et al, 1998).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Stereotypically, it is believed that smiling people look younger. For example, young people judge smiling people as being younger and sad people as being older [32]. However, a single study has shown that excessive smiling can generate an overestimation of perceived age.…”
Section: Emotional Expressionmentioning
confidence: 99%